2013
DOI: 10.1002/pi.4343
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric and electromechanical studies of plasticized poly(vinyl chloride) fabricated from plastisol

Abstract: Poly(vinyl chloride) (PVC) plastisol is used in many industrial applications and is considered an electrically inactive material. To explore the potential of plastisol as an electroactive material, the dielectric properties, space charge distribution, mechanical properties, internal structure and electromechanical behavior of plasticized PVC (PVC gel) prepared from plastisol by heating were investigated. The gel exhibited a large dielectric constant at low frequencies (1–1000 Hz), an asymmetric charge distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Below the frequency range measured here (<10 Hz), it has been reported that the conductivity of PVC gels shows a steep decrease related to the increasing charge buildup and EP at the gel-electrode interface, as is common in systems with mobile charges, only the start of this process can be seen here in the conductivity spectra of the gels at lower frequencies [39].…”
Section: Conductivity Spectramentioning
confidence: 45%
“…Below the frequency range measured here (<10 Hz), it has been reported that the conductivity of PVC gels shows a steep decrease related to the increasing charge buildup and EP at the gel-electrode interface, as is common in systems with mobile charges, only the start of this process can be seen here in the conductivity spectra of the gels at lower frequencies [39].…”
Section: Conductivity Spectramentioning
confidence: 45%
“…This hardness variation is mainly given by the percentage and type of plasticizer incorporated. [2][3][4] Plasticizers are organic compounds used to improve processability and increase the polymer flexibility of PVC by forming of dipole-dipole interactions with the polymer chains. 5 In addition, the high density of the ends of the plasticizer chains introduces additional free volume into the PVC matrix which alters properties such as viscosity, softening temperature, glass transition temperature, and modulus of elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…In this communication, we demonstrate a large deformable and reconfigurable smart varifocal lens with solventfree/green PVC (gPVC) gel. In order to find optimal gel for the varifocal lens with large deformation, we fabricated the gPVC gel via thermal mixing of PVC powder with ATBC, an environmentally benign plasticizer in various stoichiometric quantities [35][36][37]. We investigated the leakage current, dielectric constant, dielectric loss, dielectric break down voltage, and mechanical properties of the gPVC gels to select the optimal gel for large deformable varifocal lens.…”
Section: Introductionmentioning
confidence: 99%